[P263] Monte Carlo study of unflattened versus flattened 18 MV photon beam from medical linear accelerator as photoneutron source for BNCT applications. (August 2018) - Halato, Mohammed; Suliman, Ibrahim; Artoli, A.; Al-Rajhi, Mohammed; Longo, Francesco; Giannini, Gianrossano
Abstract : Purpose: Studies have shown the possibility of using photoneutron emissions from medical linear accelerator as in-hospital neutron source for Boron Neutron Capture Therapy (BNCT) [1] . In this study, the effect of removing the?attening filter from an 18-MV photon beam on photoneutron production was investigated using the Monte Carlo (MC) method. Methods: The 18-MV photon beam of Varian 2100 linear accelerator was simulated using the EGSnrc/dosxyznrc and Geant 4 MC codes. Beam dosimetric features, including depth doses, dose profiles, photon spectra distributions, photon angular distributions, photon x-y position and planner energy fluence were calculated for flattened and unflattened 18-MV photon beams. Results: The results showed that unflattened (FFF) beam has higher photon fluencies and dose rate and thus much suited for photoneutron emission. The photon fluence and relative dose for the FFF beam decrease with increasing the distance from the central axis. The amount of dose reduction at the edge of the beam increased with field size. The mean energy decreased by a factor of 1.61% and 5.4% with field size for flattened and unflattened beam, respectively. Conclusions: Because of these high photon intensities, the unflattened beam considered to be more powerful for photoneutrons production compared with the flattened beam.